Aplicación Del Modelo De Progresión Temática Derivada En La Producción Escrita De Textos Expositivos En Inglés (Ensayo Básico) - Logroño Becerra Mónica Alejandra; Rojas Castro Carmita Eulalia; Lara Olivo Lenin Iván; Guambo Yerovi Enrique Jesús (European Scientific Journal, ESJ, 2018)
This study focuses on the shortcomings affecting cohesion and coherence in English expository texts written by the students of sixth level of the Language Center of the Escuela Superior Politécnica de Chimborazo during October 2016 - March 2017. The derived thematic progression model to improve the expository texts production was the teaching strategy used by taking as a starting point the textual linguistics since it addresses to the analysis of the text as a product, in other words, the text as a coherent whole. In order to make this possible, it was conducted a quasi-experimental research, with a correlational level, and a quantitative-qualitative approach. Both, a pre -test and a post-test to the experimental and the control groups, were carried out, as well as a subsequent analysis of expository texts at the super structure, macro structure and microstructure levels. At the super structure level, the main parts of the text were identified. At the macro structure level, each of these parts was analyzed per unit of paragraph, and at the microstructure level, the grammatical structure of the different sentences of the paragraphs forming the text was also analyzed. This fact implied the identification and use of the theme-rheme elements, necessary to establish the order and logical sequence of ideas at local and global level of the text. Finally, in the process of writing was included the Derived Thematic Progression model, whose findings reported significant changes in the level of cohesion and coherence of the texts, demonstrating that this strategy may become the basis to set didactic activities to improve written production